If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2b + -4) + 14 = 26 Reorder the terms: 3(-4 + 2b) + 14 = 26 (-4 * 3 + 2b * 3) + 14 = 26 (-12 + 6b) + 14 = 26 Reorder the terms: -12 + 14 + 6b = 26 Combine like terms: -12 + 14 = 2 2 + 6b = 26 Solving 2 + 6b = 26 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 6b = 26 + -2 Combine like terms: 2 + -2 = 0 0 + 6b = 26 + -2 6b = 26 + -2 Combine like terms: 26 + -2 = 24 6b = 24 Divide each side by '6'. b = 4 Simplifying b = 4
| 42=12+5(x-1) | | 192=72x^2+24X | | 6(x+3)-75=5(x-10) | | 5-5x=-8x+14 | | (12-15)3= | | 192=72x^2+24 | | 2x+3(x-4)=(x-3) | | A+BX=CX+D | | 4(Z+7)-6=2 | | 29-(-q)=86 | | xsquared+8x-5=15 | | g-13.37=-23 | | (0.5)(y)=3 | | 5y=175 | | 3(x-1)+60=8(x+4) | | g(-3)=2x-5 | | -30+6x=x | | -19-r=-57 | | y+17.5=49 | | -1+6x+x=-85 | | Q-65=875 | | (4+3x)(2-x)+(4-3x)(2+x)=22 | | 5x-2+4x=43 | | w+-28=-17 | | -38=-x+4x-5 | | 22x=44y | | 17y-12y=25 | | 3x-4-8x+12= | | 15-4X=-X | | 3(x-3)+5=4(x-2)-10 | | 5ab-6ab+a= | | 2senx-cosx=-4 |